In Situ Thrombosis of Small Pulmonary Arteries in Pulmonary Hypertension Developing after Chemotherapy for Malignancy - Maeda, Kay; Saiki, Yoshikatsu; Yamaki, Shigeo (Pulmonary Medicine, 2015)
A few reports have provided histopathological insight into pulmonary hypertension developing after antitumor chemotherapy. In general, plexogenic pulmonary arteriopathy is a commonly observed finding in patients with severe pulmonary hypertension. We herein report a novel pathological finding that may characterize the histopathological change occurring in patients with pulmonary hypertension after chemotherapy for malignancy. Lung biopsy or autopsy was performed in 7 patients with pulmonary hypertension that developed during or after chemotherapy between 2006 and 2013 to examine the pulmonary vascular changes or to determine the cause of death. Pathological findings included in situ thrombosis in the small pulmonary arteries in 4 of 7 patients. In 2 of 4 patients, pulmonary hypertension was controlled by anticoagulants and antithrombotic agents. One patient who had organized thrombi attained spontaneous remission with oxygen therapy. The other patient died of sudden cardiopulmonary arrest during chemotherapy. Autopsy showed complete occlusion of the peripheral small pulmonary arteries and veins by thrombi. These results demonstrate that in situ thrombosis in the small pulmonary arteries could cause pulmonary hypertension after chemotherapy.